Finasowanie budowy kolejowych obiektów infrastruktury usługowej w świetle prawa pomocy publicznej — o potrzebie większej przejrzystości - Kociubiński, Jakub (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
It stands to reason that most railway infrastructure projects and all transport infrastructure for that matter are being financed by public funds. Such infrastructure addresses vital social development needs; therefore, its construction can be seen as raison d’etat. In principle, state aid can be declared compatible with the Internal Market under Article 93 of the Treaty on the Functioning of the European Union TFEU, constituting lex specialis provided for aid for transport coordination; under General Block Exemption Regulation; or directly under Article 1073 TFEU. Each of these regimes has diff erent compatibility criteria and notification requirements. This brings up the problem of delineating the boundaries between various state aid regimes.This paper provides an analysis of the convergence and divergence factors of these regimes of sectoral and horizontal aids, highlighting controversial points with regards to the interpretation of state aid rules through the lens of the jurisprudence of the Court of Justice of the European Union and European Commission’s decisions. The analysis covers the classification of state measures, controversies surrounding the Market Investor Principle and the incentive effect.
Keywords: Rail transport; EU law; state aid; Market Economy Investor Principle; incentive effect